Perancangan Helm Safety di Proyek Tol Jogja Solo dengan Metode Job Safety Analysis (JSA) - Ramsen Cahyatri Fatmasari; Dito Adi Saputra; Frysilia Tri Oktiasari; Indra Wijaya (Populer: Jurnal Penelitian Mahasiswa, 2025)
This project is motivated by the high risk of work accidents in the concrete production process, especially at night when there is poor lighting. Based on observations, there were various significant work incidents, such as injuries from sharp objects and being caught in heavy equipment, which indicate the need for increased risk control. This study aims to design personal protective equipment in the form of an innovative safety helmet using the Job Safety Analysis (JSA) method to improve occupational safety and health (K3) at PT Adhi Persada Beton Batching Plant Kebonarum. The methodology used includes hazard identification, risk analysis, and solution development in the form of designing a safety helmet that is adjusted to the ergonomic needs of workers. This study also includes analysis of work accident data, identification of potential hazards, and evaluation of the effectiveness of existing personal protective equipment. The results of the study indicate that the application of the JSA method can identify risks in a more structured manner, as well as produce recommendations for safety helmet innovations that can improve worker protection against potential hazards.